Aktivitas antioksidan ekstrak etanol rimpang curcuma xanthorrhiza Roxb. dan asam askorbat (Dengan metode DPPH, FRAP, dan H2O2) - Shannon Winnie Susanto; Monica Dewi Ranggaini (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: C. xanthorrhiza Roxb. contains chemical compounds that beneficial as antioxidant. Extraction using ethanol 70% is required to obtain these compounds. The antioxidant activity is assessed by using DPPH, FRAP, and H2O2. Parameter to interpret the value is IC50 and the value is compared to absorbic acid. Purpose: To find out the comparison of antioxidant activity between C. xanthorrhiza Roxb. extract in ethanol 70% solvent and absorbic acid using DPPH, FRAP, and H2O2 methods. Method: Using laboratory research method. Simplicia of C. xanthorrhiza Roxb. was extracted using maceration method in 70% ethanol. The antioxidant activity was tested in the sample and the absorbic acid. The samples were incubated and measured at  = 520 nm for DPPH,  = 593 nm for FRAP, and  = 510 nm for H2O2. Result: The IC50 value of C. xanthorrhiza Roxb. extract was 194,74 g/mL DPPH, 49.69 g/mL FRAP, and 166,75 g/mL H2O2 , and for absorbic acid was 0,29 g/mL DPPH, 2,78 g/mL FRAP, and 0,55 g/mL H2O2. Conclusion: FRAP method is proven to be the strongest method for measuring antioxidant activity in C. xanthorrhiza Roxb. among the other methods.